Globalisasi Sebagai Tantangan Identitas Nasional bagi Mahasiwa Surabaya - A., Syifa Syarifah; Kusuma, Ade (Global and Policy Journal of International Relations, 2016)
ABSTRACTThe era of globalization at this time causes the flow of information and the mobility of people from one area to another to move quickly. This allows human interaction between one nation with other nations is becoming increasingly intense. One of the consequences of globalization is the very strong influence of the values and the culture out of which affect people's lives, especially young people. Among the values and culture that is absorbed by the public, many of which are not in line with the values of Pancasila, so it is feared this might impact on the erosion of the values of nationalism and national identity. This study aims to see how the national identity of students Surabaya today and see the connection between globalization and national identity of students of Surabaya. This study is a qualitative research data collection methods such as focus group discussions, interviews and observation. The participants are students who study and live in the area of Surabaya. After the collected data is categorized by topics that appear to further dianalisasa using thematic analysis technique. Initial results showed that the students Surabaya positive national identity, but seen a shift in the old values are reflected in everyday life. In addition there are new values are adopted from foreign cultures as a result of globalization.Keywords: globalization, modernization, national identityDOI : https://doi.org/10.33005/jgp.v4i02.1917